PENGARUH EDUKASI PMBA TERHADAP PENINGKATAN PENGETAHUAN IBU BALITA DI KAMPUNG KELUARGA BERKUALITAS DESA TUMIANG KABUPATEN BENGKAYANG - Syabaniah, Syabaniah; Budiastutik, Indah; Marlenywati; Trisnawati, Elly (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2023)
Background: In 2022, SSGI data shows that Indonesia was 21.6% stunting, West Kalimantan 27.8%, and Bengkayang Regency 30.1%. This data shows that stunting is higher in Bengkayang Regency than in Indonesia and West Kalimantan. Intake of food is the direct cause of stunting. At 1000 HPK, intake has a significant impact on promoting growth and development in infants and toddlers. One way to reduce stunting rates is to increase knowledge about infant and child feeding (also known as PMBA). The purpose of this research is to determine the level of knowledge of mothers of toddlers in Tumiang Village, Bengkayang Regency's Quality Family Village (Kampung KB). Method: The study was conducted quasy-experimentally with a one-group pre-test and post-test design. The study's participants were 30 mothers with toddlers aged 6 to 59 months living in the Quality Family Village in Tumiang Village, Bengkayang Regency. Intervention carried out PMBA education four times in a month. Pre- and post-test questionnaires were used. The data were analysed using T-Paired. Results: The mother's knowledge level score before and after PMBA training ranged from 4.83 to 7.10. This indicates that the mother's knowledge score increased by 2.27 before and after PMBA training. The T-Paired test results in a 0.000 p-value < 0.05. Conclusion: Increasing mother's feeding knowledge before and after PMBA training can accelerate stunting reduction in Quality Family Village, Tumiang Village, Bengkayang Regency. Advice: PMBA training for toddler mothers can prevent stunting. Keywords: Knowledge of Mothers, PMBA Education, Quality Family Village, Stunting, Tumiang Village